Pengaruh Online Customer Review di E-Commerce Shopee terhadap Keputusan Pembelian Produk Fashion Dama KAra - Azizah, Mutiara Tsani; Wirakanda, Gugum Gumilang (Jurnal Manajemen dan Pemasaran, 2024)
This study aims to determine consumer assessment of the brand on Shopee and to determine the influence of online customer reviews on the purchasing decisions of Dama Kara fashion products on Shopee. Using a descriptive method with a quantitative approach, the data analysis technique used is simple linear regression. The sampling technique used is accidental sampling, with 96 respondents. The results of the study show that Online Customer Reviews have a positive and significant effect on the Purchasing Decisions of Dama Kara Fashion products by 83.8%.